2007
DOI: 10.3140/bull.geosci.2007.01.051
|View full text |Cite
|
Sign up to set email alerts
|

The arborescent Linopteris obliqua plant (Medullosales, Pennsylvanian)

Abstract: The foliar morphospecies Linopteris obliqua (Bunbury) Zeiller, 1899 was originally based on isolated pinnules from Middle Pennsylvanian (upper Westphalian) strata in the Sydney Coalfield in Nova Scotia, Canada. However, new finds from the type area, including segments of a cauline axis and some fronds, attached juvenile croziers, an attached ovule, and associated pre-pollen organ, allow for a more complete understanding of the whole Linopteris obliqua plant. It was arborescent, 9 m to 10 m tall, with fronds ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The association of pinnules of different shapes indicates that these pinnules come from the same species, but from different parts of the plant. This phenomenon is also shown in Zodrow et al (2007). Figure 1 on the Plate XVII shows two poorly preserved pollen organs in organic connection to a rachis with some Linopteris obliqua pinnules still attached.…”
Section: Division: Gymnospermopsidasupporting
confidence: 53%
See 3 more Smart Citations
“…The association of pinnules of different shapes indicates that these pinnules come from the same species, but from different parts of the plant. This phenomenon is also shown in Zodrow et al (2007). Figure 1 on the Plate XVII shows two poorly preserved pollen organs in organic connection to a rachis with some Linopteris obliqua pinnules still attached.…”
Section: Division: Gymnospermopsidasupporting
confidence: 53%
“…The pinnules identified as L. neuropteroides are mixed with pinnules, which are referred to L. obliqua on the same specimen. Venation diagrams of the pinnules made by camera lucida show some differences between pinnules preserved showing the adaxial and abaxial sides, as already described by Zodrow et al (2007). Due to this fact we assume that only one linopterid species inhabited the original environment.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Slender upright trees, rooted in ostracod-rich gray shale (Unit 3), are most likely medullosalean pteridosperms given their close association with the foliage of Alethopteris, Laveineopteris, and Paripteris. These three genera (or their close relatives) have been reconstructed as small trees and shrubs (Pfefferkorn et al, 1984;Shute and Cleal, 2002;Zodrow et al, 2007), consistent with the observed woody stumps, and the same three genera have been interpreted as fringing coastlines in the Lower Pennsylvanian Lancaster Formation ('Fern Ledges') in New Brunswick (Falcon-Lang and Miller, 2007). To what degree this medullosalean-dominated coastal vegetation was saline-tolerant is uncertain (Stull et al, 2012) rhomboideus shares features with some progymnosperms, and "S." valida is similar to the putative noeggerathialean Palaeopteridium michiganensis (cf.…”
Section: Coastal Vegetationmentioning
confidence: 99%